Hubungan Antara Pengetahuan Orang Tua Terhadap Perilaku Pencegahan Diare Pada Balita Di Poli Anak RSKD Ibu Dan Anak Pertiwi Makassar - Asmiana Saputri Ilyas; Yayu Angriani (LPPM STIK Makassar, 2021)
Morbidity and mortality rates of diarrheal disease are still high. Nurses as health workers can contribute in the handling of diarrhea in accordance with its role, one of which is to provide education to parents, especially mothers for the prevention of diarrheal diseases. The purpose of this study was to find out the relationship between the knowledge of parents in the prevention of diarrhea in the poly children RSKD mother and child pertiwi Makassar. This research is a descriptive analytical research with cross sectional method. The population in the study was the parents of toddlers suffering from diarrhea and a sample of 30 people. Data analysis with univariate and bivariate analysis using Chi-Square statistic. Based on the results of the study showed that the statistic test using chi-squaretest, with alternative continuity correction test obtained value p= 0.030 (p<0.05) which means H1 received or there is a relationship between parental knowledge to diarrhea prevention behavior in child poly RSKD Mother And Child Pertiwi Makassar.